Tingkat keberhasilan inseminasi buatan (IB) berdasarkan Program Sapi Induk Wajib Bunting (SIWAB) di Kecamatan Sangkub - Mahyun, J.C.; Poli, Z.; Lomboan, A.; Ngangi, L.R. (ZOOTEC, 2021)
ARTIFICIAL INSEMINATION (AI) SUCCESSFUL RATE UNDER THE MANDATORY PREGNANT CATTLE PROGRAM (SIWAB) IN SANGKUB REGENCY. This type of research is an explanatory research survey, explaining the successful rate of AI through the compulsory pregnancy cows (SIWAB) program in Sangkub District, Bolaang Mongondow Utara Regency. The purpose of the survey is to collect some data through interview measurement tools. The types of data in this study were the primary data and secondary data. Primary data were collected directly from respondents. The sample selection was determined purposively involving breeders who had productive female cows in Sidodadi, Pangkusa and East Sangkub villages as many as 30 respondents. The primary data technical application consist of several ways, including questionnaires, interviews, and observations. The results showed that the level of trust in the AI based on the SIWAB program in Sangkub Regency, mainly response of breeders to AI technology was very good with evidence of their participation in including productive cows in the SIWAB program. Whereas for acceptors / female cows participating in the SIWAB program in Sangkub Regency, mainly female cows showed 66 head productivity. For Service per Conception variable on 66 cows included in the SIWAB program produced 58 cows of one service of AI and 8 heads of two services of AI obtaining 1.12%. From the total number of cattle included in the SIWAB (IB) program in Sangkub Regency, the 66 cows were successfully pregnant and gave birth of 66 calves. Based on the analysis and results discussion, it can be concluded that generallyl the Breeder Response, Service per Conception, Conception Number, and ABL to the SIWAB program in Sangkub District were included in the good category.Keywords: Beef cattle, artificial insemination, compulsory pregnancy cows, Sangkub district.